2015
DOI: 10.3109/09687637.2015.1030355
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for prescription drug misuse among young adults: Considering social and developmental contexts

Abstract: Aims As part of a larger study on prescription drug misuse among young adults active in urban nightlife scenes, we examined participants’ motivations for misuse. Prescription painkillers, stimulants and sedatives were the primary substances of interest. Methods Participants were recruited from nightlife venues in New York using time-space sampling. Subjects completed a mixed-methods assessment at project research offices. The data presented here are from a subsample of 70 qualitative interviews conducted dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
17
0
5
Order By: Relevance
“…25,30 One recent qualitative study involving 70 young adults in New York City found that prescription opioids are normalized in young people’s social networks, particularly to “intensify” the experience of relaxing or hanging out with friends. 31 Collectively, these and our results suggest that clinicians, harm reduction providers, and policymakers should be cognizant of the social meanings ascribed to prescription opioid misuse among young adults in addition to individual motivations for NMPO use. Additionally, studies have suggested that interventions seeking to prevent the harms of opioid misuse must begin during the teen years when experimentation with opioid misuse first begins, well before first heroin use.…”
Section: Discussionmentioning
confidence: 55%
“…25,30 One recent qualitative study involving 70 young adults in New York City found that prescription opioids are normalized in young people’s social networks, particularly to “intensify” the experience of relaxing or hanging out with friends. 31 Collectively, these and our results suggest that clinicians, harm reduction providers, and policymakers should be cognizant of the social meanings ascribed to prescription opioid misuse among young adults in addition to individual motivations for NMPO use. Additionally, studies have suggested that interventions seeking to prevent the harms of opioid misuse must begin during the teen years when experimentation with opioid misuse first begins, well before first heroin use.…”
Section: Discussionmentioning
confidence: 55%
“…The anonymity of the questionnaires was guaranteed to elevate the validity of self-reports of stigmatized behaviors [23], and our research assistants administered these questionnaires during a regular class period without the presence of teachers (to avoid any potential information bias). Of the total sample, 51.5% (12,526) were boys, and the mean age of the students was 15.2 ± 1.8 years. The study procedures were carried out in accordance with the Declaration of Helsinki.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…I løbet af de sidste 20 år er ikke-medicinsk brug af receptpligtig medicin for kognitiv optimering eller forbedring (herefter IMRMK) øget blandt unge. Både forekomst og stigning er specielt blevet dokumenteret blandt college-studerende i USA og andre vestlige lande (Boyd et al, 2009;Forlini & Racine;, LeClair et al, 2015Maier & Schaub, 2015;McCabe et al, 2005McCabe et al, , 2014Petersen, 2015;Rabiner et al, 2009;Teter et al, 2010Teter et al, , 2012Varga, 2012). Studier estimerer således, at mellem 7 % og 34 % af college-studerende i USA bruger medicin som Adderal™ og/eller Ritalin™ 1 for at forbedre deres akademiske praestationer (Hall et al, 2005;McCabe et al, 2006;Varga, 2012, White et al, 2005SAMSHA, 2013;LeClair et al, 2015).…”
Section: Baggrundunclassified
“…Samtidigt er et stigende antal børn, teenagere og unge voksne blevet diagnosticeret og medicinsk behandlet for sygdomme som ADHD, depression og angst (Ford et al, 2014;Hamilton, 2009;Jørgensen, 2012;Roy et al, 2011), og mange forskere ser en sammenhaeng mellem øget diagnosticering og tilgaengelighed af medicin blandt børn og unge voksne (DeSantis & Hane, 2010;LeClair et al, 2015;McCabe et al, 2007;Mui et al, 2014) og stigningen i ikke-medicinsk brug blandt unge studerende.…”
Section: Baggrundunclassified